2015
DOI: 10.1016/j.wear.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Mapping wear mechanisms of TiC/Ti composite coatings

Abstract: In this work, a fundamental study of the wear transition regimes with respect to sliding speed and normal load was carried out for a pin-on-disk sliding couple, involving hardened steel (disks) and titanium base titanium carbide composite coatings (pins). The coating was deposited using a Tungsten Inert Gas (TIG) welding torch melting process. The sliding speed was varied from 0.38 to 1.5m s-1, and the normal load was varied from 10 to 50N. Dry sliding wear behaviour of the disks was characterized by abrasive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 35 publications
(40 reference statements)
0
24
0
1
Order By: Relevance
“…In view of the tests results, a slurry erosion wear mechanistic map has been developed. Wear mechanistic maps [27][28][29][30] can be useful tools to identify various wear mechanisms encountered over the range of tests parameters. This may be helpful in the selection of materials, designing of tidal turbine blades, and defining operational limits.…”
Section: Erosion Mechanism Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the tests results, a slurry erosion wear mechanistic map has been developed. Wear mechanistic maps [27][28][29][30] can be useful tools to identify various wear mechanisms encountered over the range of tests parameters. This may be helpful in the selection of materials, designing of tidal turbine blades, and defining operational limits.…”
Section: Erosion Mechanism Mapmentioning
confidence: 99%
“…In this study, a G10 epoxy glass laminate composite has been tested for its erosion resistance during sub-sea conditions. The synergistic effects and erosive wear mechanisms have been studied on the basis of mass loss, SEM micrographs of the surfaces, EDX analysis and related research work found in the literature using wear mechanisms map techniques [27][28][29][30]. Further work will be to compare with tribological performance of different types of composite materials and coatings to evaluate the optimum material for the range of environmental conditions encountered in service.…”
Section: Introductionmentioning
confidence: 99%
“…These maps indicate the transitions in the degradation level of the specimen with the changes in operating conditions. Approximated wear-modes transition boundaries are highlighted on these maps, which identify the mode of degradation, establish the level of wastage rate and potential ''safe'' and "unsafe" operation conditions of a tribosystem [16][17][18][19][20][21].…”
Section: Erosion Mode Mapsmentioning
confidence: 99%
“…However, the addition of ceramic particles into titanium and its alloys is an effective method to improve the wear resistance. Some reports on the dry sliding wear behavior of titanium matrix composites (TMC) with pure Ti or titanium alloys have been published (Threrujirapapong, et al, 2008, Chang, et al, 2013, Luo, et al, 2014, Rasool, et al, 2015 . Most of these studies used Ti-6Al-4V alloy as a matrix material (Alman, et al, 1999, Alma, et al, 2002, Candel, el at., 2010, Hu, el at., 2010, Mahamood, et al, 2013, Xie, et al, 2014.…”
Section: Introductionmentioning
confidence: 99%